2021
DOI: 10.3390/pharmaceutics13040526
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Flavonoids from Fruits of Morus alba Promoting Insulin-Stimulated Glucose Uptake via Akt and AMP-Activated Protein Kinase Activation in 3T3-L1 Adipocytes

Abstract: Morus alba (Moraceae), known as white mulberry, has been used to treat fever, protect against liver damage, improve eyesight, and lower blood sugar levels in traditional oriental medicine. Few studies have been conducted on the antidiabetic compounds identified from M. alba and their underlying mechanisms of action. Consequently, in this study, the fruits of M. alba were investigated for potential antidiabetic natural products using 3T3-L1 adipocytes. Phytochemical analysis of the ethanolic extract of M. alba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…At present, antidiabetic drugs such as biguanides, sulfonylureas, meglitinides, thiazolidinediones, dipeptidyl peptidase IV inhibitors, and α -glucosidase inhibitors have many side effects, such as weight gain, hypoglycemia, gastrointestinal disorders, liver and kidney damage, and hypersensitivity reactions [ 15 ]. On the other hand, plants rich in certain types of flavonoids and other phenolics can exert a significant impact on diabetes via protecting pancreatic islet B cells, reducing the absorption of glucose in the digestive tract, and promoting glucose uptake in adipocytes [ 16 , 17 , 18 ]. Therefore, natural products from medicinal plants might have a good development prospect in the field of diabetes treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At present, antidiabetic drugs such as biguanides, sulfonylureas, meglitinides, thiazolidinediones, dipeptidyl peptidase IV inhibitors, and α -glucosidase inhibitors have many side effects, such as weight gain, hypoglycemia, gastrointestinal disorders, liver and kidney damage, and hypersensitivity reactions [ 15 ]. On the other hand, plants rich in certain types of flavonoids and other phenolics can exert a significant impact on diabetes via protecting pancreatic islet B cells, reducing the absorption of glucose in the digestive tract, and promoting glucose uptake in adipocytes [ 16 , 17 , 18 ]. Therefore, natural products from medicinal plants might have a good development prospect in the field of diabetes treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Both compounds, rutin, and quercetin-3-O-β-D-glucoside (Q3G), have been shown to enhance glucose uptake through the AKT-mediated insulin signaling pathway or AMP-activated protein kinase activation (AMPK) in 3T3L1 adipocytes and could potentially be used in therapy for T2DM management. 11 In addition to rutin, the leaves of Morus alba contain apigenin, quercetin-3-triglyceride, lupeol, β-sitosterol, moracetin, isoquercitrin, coumarin, volatile oil, alkaloids, amino acids, and organic acids, proving the hypoglycemic properties and their effect enhancer on diabetic nephropathy. 24 Four main chemical components were identified in the ethanol extract of Morus alba : chlorogenic acid, rutin, isoquercitrin, and quercitrin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies carried out to date on the antidiabetic compounds in this product are insufficient. 11 …”
Section: Introductionmentioning
confidence: 99%
“…These natural chemicals have a lot of pharmacological power. This subclass was chosen since numerous studies have revealed that such compounds possess a variety of beneficial properties, such as anti-diabetic, anti-oxidant, antitumor, cardioprotective and anti-inflammatory activities, in addition to anti-cancer, anti-allergy, anti-mutagenesis, antimicrobial and antiviral activities [ 5 ]. Flavonoids’ potential to alter the insulin signaling pathway in typical target tissues such as muscle, liver and adipose tissue has been shown in abundant scientific studies to help prevent or alleviate insulin resistance in diabetics [ 6 ].…”
Section: Introductionmentioning
confidence: 99%